THE USE OF SMALL GROUP DISCUSSION USING MEDIA VIDEO TO DEVELOP STUDENTS READING SKILL - Febriyanti Sumarauw; Elisabeth Z. Oroh; Rinny Rorimpandey (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of this research was to ascertain whether or not an approach using small-group discussion aided by video-based media may be effective in enhancing students' reading abilities. In order to boost students' reading abilities, an activity in which they work in small groups to watch videos of the topic being covered is used. Researchers used quantitative research through pre-experimental design with one group pre-test and post-test design and the sample of this study was class VIII students of SMP Negeri 1 Eris totaling 20 students. In this study, researchers employed a multiple-choice questionnaire. The average score formula was used for the statistical analysis of the study's data. Students' average score improved from 36 on the pre-test to 78 on the post-test, according to the statistics. Student performance improved by a mean of 42 points between the pre- and post-tests. Students' post-test scores, on average, were found to be greater than their pre-test scores. The study's author, therefore, drew the inference that including video-based, small-group discussions into the process of teaching reading may be effective.